PERSEPSI GURU TENTANG PENERAPAN MANAJEMEN SUMBER DAYA MANUSIA DENGAN EFEKTIVITAS KERJA GURU - Tiara Tiara Fur Qonita (Hijri, 2018)
The  purpose  of  this  research  is  to  know  the  1).  Knowing  the  perceptions  ofteachers towards the application of human resources management that are in SMK PAB 2 Helvetia Medan Labuhan Deli, 2). Find out the effectiveness of the work of the teacher in, 3). Knowing there is a signifikankah relationship between the perception of teachers about the application of human resources management with the effectiveness of the work of the teacher in. The results of this study concluded that there is a data management based on strong relationships and significant among teachers about the application of human resources management (X) and the effectiveness of the Work of teachers (Y) of 0076 with coefficient determination (r2) are obtained from the results of the calculations of0.006 which give meaning to that perception of teachers about the application of human resources management (X) gives the relationship of 0.006 x 100% = 0.6% against the effectiveness of the work of teachers (Y). The results of this study concluded that there is a data management based on strong relationships and significant among Prsepsi teachers about the application of human resources management (X) and the effectiveness of the Work of teachers (Y) of 0076 with coefficient determination (r2) are obtained from the results of the calculations of0.006 which give meaning to that perception of teachers about the application of human resources management (X) gives the relationship of 0.006 x 100% = 0.6% against the effectiveness of the work of teachers (Y). While the perception of teachers about the application of human resources management has a strong and significant relationship with the effectiveness of the work of the teacher in PAB 2 Helvetia Labuhan Deli Sub with the results of the analysis of the hypothesis it is characterized with a donation effect of 1%. While the significant value was briefly engaged both (Teacher Perceptions about the implementation of human resources management and the effectiveness of the work of the teacher) can be seen through the test of ' t ". The t has done turns out obtained t calculate = 4.272 while values t = table 2.048. Therefore t count (4,272) > t table (2.048), this indicates that there is a strong relationship between variables and significant Teacher Perceptions about the implementation of human resources management with the effectiveness of teacher's Work with linear relationships form and Predictive through the line korelasiŶ = 23.523 + 74.975 X, this correlation equation of a line explaining that if Teachers perceptions of factors about the application of human resources management increased by one unit then the effectiveness of the Work of teachers will also increase sebesar74 , 975 + 23.523 =100.498 units. Keywords: Teacher Perceptions About The Implementation Of Human Resources Management, The Effectiveness Of The Work Of Teachers